Exercise Serum Alters Genes Related Mitochondria in Cardiomyocyte Culture Cell - Lesmana, Ronny; Prasetyo, Wibowo Budi; Ray, Hamidie Ronald Daniel; Tarawan, Vita Murniati; Goenawan, Hanna; Setiawan, Iwan; Pratiwi, Yuni Susanti; Juliati, Nova Sylviana; Supratman, Unang (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
Exercise-induced hearth muscle adaptation is important for physiological process after exercise. This adaptation will ensure basal mitochondrial homeostasis and as a part of the mitochondria quality control. This process is reflected by equal level of biogenesis stimulation and as well as the selective degradation of old and undesirable mitochondria through fusion or fission cycle and Mitophagy. There is limited information about genetic regulation stimulated by training in cardiomyocytes. We believe there is a specific myokines or protein release in the serum and initiate cardiac muscle adaptation process. In the present study, twelve male wistar rats were appointed to two group: sedentary control and aerobic-intensity (AE, 15m/minute). Rats were trained for running with specific protocol as follows: 30 minutes/day with a 5 times/week interval for 8 weeks. On the last day, serum form control and exercise groups were taken via retro-orbital sinus. Then, 3.105 H9C2 cells (Rat cardiomyocytes cell line) were cultured and incubated by this serum for 24 hours. After treatment, cell were extracted using trisure for RNA purification and continue with reverse transcriptase PCR. Our data showed that expression of the Pgc-1α, Mfn1, Mfn2, Opa1, Drp1, Pink, and Parkin genes were altered and modulated. Specifically, Mfn1, Mfn2, and Opa1 gene expression levels significantly increased. Interestingly, we did not find significant modulation for Pgc-1α, Drp1, Pink, and Parkin. Taken together, serum of exercise rats might be contained with myokines or specific protein which was released during training and it altered mitochondrial genes expression in cardiomyocytes culture cell. We believe that myokines release in the serum had a contribution in cardiacmyocyte adaptation.